Preparation and Characterization of TiO2 Nanoparticles via a Sol- gel Method - satar, maryam; Olfat A. Mahmood; Zainab N. Jameel (ASJ - Academic Science Journal, 2025)
TiO2 nanoparticles (NPs) were prepared by the sol-gel method by using TiCl4 as a starting material, whereas the applied temperatures were 450 °C and 900 °C. The XRD results showed that nanoparticle (TiO2 NPs) anatase and rutile phases had a polycrystalline nature with a tetragonal structure. FESEM results showed the formation of nanostructures with cauliflower and irregular shapes with average particle sizes of 36.9 nm and 58 nm for the Anatase and Rutile phases, respectively. The EDS spectra showed that the elements present in the synthesized TiO2 NP (anatase and rutile) phases were Ti and oxygen O. The FTIR spectra of TiO2 NPs showed the presence of broadband at 450–4000 cm−1 corresponding to the stretching vibration of terminating hydroxyl groups in the samples. The UV‒Vis-NIR absorbance spectra were recorded in the range of 300–900 nm to investigate the optical characteristics. Results showed that the absorption of TiO2 in the Anatase phase is less than that of TiO2 in the Rutile phase. The optical energy gaps were 3.05 and 2.7 eV for the Anatase and Rutile phases, respectively. Keywords: TiO2, Anatase phase, Rutile phase, FE-SEM, EDS.